Flexible manufacturing systems in practice applications, design, and simulation - Talavage, Joseph (Manufacturing engineering and materials processing (Marcel Dekker, Inc.), 1988)
This authoritative guide provides a logical, progressive overview of the industrial realities of flexible manufacturing and will prove invaluable for manufacturing, industrial, production, design, mechanical systems, and operations engineers.